2018
DOI: 10.1021/acs.jpcc.7b09272
|View full text |Cite
|
Sign up to set email alerts
|

A DFT Study on the Catalytic CO Oxidative Coupling to Dimethyl Oxalate on Al-Doped Core–Shell Pd Clusters

Abstract: A series of core–shell catalysts aiming at CO oxidative coupling to dimethyl oxalate (DMO) were constructed, and effects of the second metal doping and surface structures on the reaction activity and favorable reaction path were investigated by using the density functional theory (DFT) method. Pd13, Al@Pd12, and Ag@Pd12 were first studied to find the proper doping metal. Our results showed that the activity of CO oxidative coupling to DMO follows the order of Al@Pd12 > Pd13 > Ag@Pd12, and the same result was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Moreover, similar conclusions have also been verified by the relevant DFT calculations. Surface electronic properties of precious metal core/shell nanostructures were investigated to explain the effects on catalytic activity. , ,, Charge transfer between atoms, ε HOMO variation, coverage differences, d-band center shift, and other changes in surface electronic structures caused by different core/shell combinations will have a huge impact on different reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, similar conclusions have also been verified by the relevant DFT calculations. Surface electronic properties of precious metal core/shell nanostructures were investigated to explain the effects on catalytic activity. , ,, Charge transfer between atoms, ε HOMO variation, coverage differences, d-band center shift, and other changes in surface electronic structures caused by different core/shell combinations will have a huge impact on different reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, a core/shell structure shows enhanced catalytic properties relative to their alloy because of its highly functional architecture . The energetic and electronic properties of different elements and compositions were already investigated by density functional theory to confirm the superior activity of the core/shell structure, and it was found that properties such as Fermi energy and d-band center were strongly correlated with the activity for different reactions. However, the synthesis of bimetallic core/shell components is a complex process, and hence, there are various strategies available for producing different kinds of catalysis . A multistep seed-mediated method is often used to form the regular core/shell structure. In a relatively simple one-pot preparation, surfactants, ionic liquids, , etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 20 years, many research groups have carried out detailed research on this topic. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Similarly, in the hydrogenation of DMO, the performance of Cu catalyst is also the most critical part. In the past few years, researchers have also conducted in-depth research on this key technology.…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamic assessment for the Al-Co-Pd ternary system has not yet been published. However, the system is of interest for the possible use of the Al-Pd based materials, for example, for catalysts [1] or as coatings with good oxidation resistance, low adhesion and high hardness [2][3][4] and also in electronics as semiconductors [5,6]. In addition, the system is also interesting from a scientific point of view because it contains a large number of complicated intermetallics, quasicrystals and quasi-crystalline approximants [7,8].…”
Section: Introductionmentioning
confidence: 99%